A new species of Bryaxis Kugelann, 1794 (Coleoptera: Staphylinidae: Pselaphinae) from Vietnam - Mizerakis, Vangelis; Hlaváč, Peter; Faille, Arnaud (Zootaxa, 2025)
A new species, Bryaxis phiaoaci sp. nov. from Phia Oac National Park in northern Vietnam, is described. This is the first species of this genus described from Vietnam.